Analysis of Liquid Loading and Sandness in Gas Wells A1, A2 And Their Correction with The Plunger Lift Method in Field B - Musnal, Ali; Melysa, Richa (Journal of Earth Energy Engineering, 2023)
The inability of the gas to lift liquid to the surface causes liquid to accumulate in the downhole, this event is called liquid loading, and sand deposits at the bottom of the well are caused to be swept away by the gas flow. If a well has liquid loading and sandification, well production will decrease and even the well will die. For this reason, it is necessary to carry out a predictive analysis of the well and a method to overcome the problem of liquid loading and sandiness using a plunger lift. Liquid loading is not always easy to identify, because the well is still producing significantly. The method used in the petroleum world to identify liquid loading is the "Turner et al" method. The plunger is a piston-type device that moves freely in the tubing and according to the inside diameter of the pipe, rising when the well pressure is sufficient to lift it and moving back down due to the force of gravity. The plunger lifting system uses gas pressure buildup in the well to lift the accumulated liquid column out of the well. The researcher conducted a liquid loading analysis on well A1 and well A2. From the results of the study it was identified that well A1 did not experience liquid loading, because the calculation results showed that the well's critical gas flow rate was 3.3 MMSCFPD which was less than the actual gas flow rate of 5 MMSCFPD. Well A2 is experiencing liquid loading, because the results of the calculation of the well's critical gas flow rate are 3.6 MMSCFPD, while the actual gas flow rate in the field is 3MMSCFPD. After removal of fluid and sand from the bottom of the well, the production rate of the A2 gas well increased to 5 MMSCFPD.